Uridine 5'‑diphospho‑glucronosyltrasferase: Its role in pharmacogenomics and human disease (Review) - Sánchez Domínguez, Celia Nohemí; Gallardo Blanco, Hugo Leonid; Salinas Santander, Mauricio Andrés; Ortiz López, Rocío (2018)
Abstract. Biotransformation is an enzyme-catalyzed process in which the body converts endogenous compounds, xenobiotics and toxic substances into harmless or easily excreted metabolites. The biotransformation reactions are classified as phase I and II reactions. Uridine 5'-diphospho (UDP)-glucuronosyltransferases (UGTs) are a superfamily of phase II enzymes which have roles in the conjugation of xenobiotics or endogenous compounds, including drugs and bilirubin, with glucuronic acid to make them easier to excrete. The method the human body uses to achieve glucuronidation may be affected by a large interindividual variation due to changes in the sequences of the genes encoding these enzymes. In the last five years, the study of the genetic variants of the UGTs at a molecular level has become important due to its association with several diseases and the ability to predict adverse events due to drug metabolism. In the present review, the structure and the prominent genetic variants of the UGT1A subfamily and their metabolic and clinical implications are described.